HEAT TRANSFER AND FLOW PROFILES IN ROUND TUBE HEAT EXCHANGER EQUIPPED WITH VARIOUS V-RINGS - Boonloi, Amnart; Jedsadaratanachai, Withada (My University, 2022)
This study numerically investigates pressure loss, heat transfer and thermal efficiency in round tube heat exchangers attached with various types of V-rings. A typical type A V-ring is compared with two types of modified V-rings (type B and C). The impacts of blockage ratios, b/D = 0.05, 0.10, 0.15 and 0.20 for all V-ring types in the turbulent region are discussed (Re = 3000 – 20,000). Flow directions in the round pipe attached with the V-rings are varied. The V-apex setting downstream is referred to as “V-Downstream, while the V-apex setting upstream is referred to as “V-Upstream”. The flow and heat transfer profiles in the tested section are analyzed using the finite volume method (a commercial code with the SIMPLE algorithm). The thermal performance of the tested tube is measured in terms of dimensionless variables: thermal enhancement factor (TEF), Nusselt number (Nu) and friction factor (f). Numerical results reveal that type B and C V-rings can reduce pressure drop compared with type A V-ring. Additionally, the V-Upstream of type C V-ring yields the maximum TEF of 3.10 at b/D = 0.05.
Keywords: Nusselt number; Pressure drop; Thermal efficiency; Turbulator; V-ring